“A MINUTE TO CLEAN IT”: COMPLIANCE TO HAND WASHING PRACTICE AMONG HEALTHCARE WORKERS IN ILIGAN CITY - Atienza, Beaven; Barrato, Jannette; Gabilan, Gerlie; Gacal, Stephen; Marin, Maizl; Escabarte, Art (PEOPLE: International Journal of Social Sciences, 2017)
Background:Healthcare-associated infections are the most common adverse event in healthcare, resulting in a significant burden on patients, their families, and health care systems. Hand hygiene is the leading measure for preventing the spread of pathogens and reducing health care associated infections, but health care providers’ adherence to recommended practices remains suboptimal in most settings, and (improvement) maintaining its standards is difficult to sustain.Objective: This study attempts to explore the degree of compliance among nurses and nursing attendants in the strict implementation of the standards in hand washing practices. Methodology: Quantitative-quasi-experimental design was used to measure their degree of compliance of proper hand hygiene. Using a questionnaire based on the World Health Organization’s “My Five Moments of Hand Hygiene”. Convenience sampling was used in choosing 50 nurses and nursing attendants in selected wards of a hospital in Iligan City. Weighted Mean and Spearman-Rank Correlation was used as statistical tool. The data was encoded for analysis using the IBM-SPSS version 20 software. This study showed that out of the five moments of hand hygiene, (After Body Fluid Exposure Risk Moment) was the most practiced moment of hand washing. This is followed by the (After Touching the Patient Moment). The (Before Clean/ Aseptic Procedure Moment) and (After Touching Patient Surrounding Moment) was tied on third place. Only the (Before Touching a Patient Moment) fell into the “frequently” parameter. The study implies that the respondents were usually compliant to hand washing practices. Strict monitoring and implementation of hand washing protocol must be constantly observed.